Acute kidney injury in tenofovir exposed patients in HIV infected individuals admitted at Groote Schuur hospital, Cape Town and Livingstone hospital, Gqeberha, South Africa - Mazondwa, Simthandile Fiona (Department of Medicine, 2022)
Introduction: Tenofovir disoproxil fumarate (TDF) is vastly used in South Africa (SA) as a first line agent for the treatment of human immunodeficiency virus (HIV). TDF is known to be associated with nephrotoxicity with identified risk factors. This study aimed to describe the demographics, clinico-biochemical features, kidney function and mortality outcomes in TDF exposed patients with acute kidney injury (AKI) in two tertiary centres in SA. Method: This observational cohort study reviewed all HIV infected in-patients presenting with AKI referred to the nephrology units at both Groote Schuur Hospital, Cape Town and Livingstone hospital, Gqeberha. Baseline characteristics, contributory factors to the AKI, associated clinical and biochemical features were recorded. Where a kidney biopsy was indicated, histological features were documented. Kidney and mortality outcomes of the enrolled patients were assessed over a 1-year period. Results: There were 213 patients enrolled from 1 August 2013 to 30 September 2016, 114/213 (51.8%) of the patients were TDF-exposed and 99/213 (45%) were TDF-unexposed. The median age was 37 years (IQR: 31 - 45yrs). The TDF-exposed were significantly older, 40 years versus 34 years (p<0.01) The TDF-unexposed group had a higher prevalence of hypertension: 21/99 (21.2%) versus 11/114 (9.7%), (p=0.02). The median creatinine at referral was 642 µmol/L (IQR: 340 - 1116 µmol/L) and 96/210 (45.7%) required dialysis. HIV/tuberculosis (TB) coinfection was common, 119/199 (59.8%). There was significant exposure to nephrotoxic drugs and drugs associated with idiosyncratic drug reactions in both groups, with anti-tuberculous treatment being the most common. Rifampicin was used by 51/212 (24.1%) [TDF-exposed 31/114 (27.2%) and TDF-unexposed 20/98 (20.4%), p=0.25]. There were no differences in serum and urinary biochemical features between the TDFexposed and unexposed groups. Of the enrolled patients, 57/213 (26.8%) underwent a kidney biopsy. On histology, the incidence of acute tubular necrosis (ATN) was higher in TDFexposed individuals (TDF-exposed: 47% versus TDF-unexposed: 22% p=0.05) whilst in TDF-unexposed, HIV associated nephropathy was most common. In the total cohort, chronic kidney disease (CKD) developed in 22/212 (10.4%) and the mortality was 62/213 (29.1%). There were no significant differences between the TDF-exposed and non-exposed cohorts in terms of CKD or mortality. Conclusion: This study demonstrated that hospitalized people living with HIV in SA have a high rate of tuberculosis co-infection and significant drug exposures. The clinical characteristics, severity of AKI and outcomes were similar in TDF-exposed and -unexposed. TDF exposure was associated with a greater degree of ATN on kidney biopsy. AKI in this HIV infected cohort carried a high mortality, regardless of the aetiology.medicib